Kemampuan Berpikir Kreatif Siswa dalam Pemecahan Masalah dengan Konteks Covid-19 - Julia Ayu Wulandari; Tatag Yuli Eko Siswono (Jurnal Tadris Matematika, 2021)
This study aims to describe the creative thinking abilities of students based on their level of creative thinking in solving math problems in the context of Covid-19. Data collection was carried out by providing a test for solving mathematics problems in the context of Covid-19. Data analysis techniques were data reduction, data presentation, and conclusion drawing. Data analysis is to see how the student is solving problems with what ideas can be given. The research subjects were four students with different levels of creative thinking, then interviewed how the students completed these problems. The results showed that the subject at level 0 (not creative) only gave one answer and one way of solving the problem. Subjects with creative thinking level 1 (less creative), able to produce two different answers, and able to present data in two ways of presenting data, but only one is correct. Then the subject with level 2 (creative enough), can give one answer correctly and two ways of presenting the data correctly. While the subject with level 3 (creative) thinking can produce two different answers correctly and two ways of presenting data correctly.